2013
DOI: 10.1371/journal.pone.0077047
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Improves Drought Tolerance in Arabidopsis thaliana by MicroRNA Expressions

Abstract: Hydrogen sulfide (H2S) is a gasotransmitter and plays an important role in many physiological processes in mammals. Studies of its functions in plants are attracting ever growing interest, for example, its ability to enhance drought resistance in Arabidopsis. A general role of microRNAs (miRNAs) in plant adaptive responses to drought stress has thereby increased our interest to delve into the possible interplay between H2S and miRNAs. Our results showed that treating wild type (WT) Arabidopsis seedlings with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 37 publications
1
62
0
1
Order By: Relevance
“…The trends of the expression pattern were consistent with those reported by other investigators for salt, drought stresses as well as pathogen infection (Liu et al 2008Xin et al 2010;Khraiwesh et al 2012). The expression trends of target genes SpGRF1 and SpGRF3 were similar to previous studies after salt and drought stress (Shen et al 2013;Wang et al 2013). These findings suggested that miR396a may be potentially connected with stress responses in plants that are vital for survival in a harsh environment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The trends of the expression pattern were consistent with those reported by other investigators for salt, drought stresses as well as pathogen infection (Liu et al 2008Xin et al 2010;Khraiwesh et al 2012). The expression trends of target genes SpGRF1 and SpGRF3 were similar to previous studies after salt and drought stress (Shen et al 2013;Wang et al 2013). These findings suggested that miR396a may be potentially connected with stress responses in plants that are vital for survival in a harsh environment.…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies, heterologous expression of athmiR396a has been reported in tobacco and resulted in reduction of the expression of three NtGRF genes ). The expression levels of GRF1 and GRF3 have been reported to significant down-regulated under drought stress in A. thaliana (Shen et al 2013).The miR396-GRF1 show significant regulation relationship in roots and leaves under salt and PEG concentrations in cotton ). Overexpression of miR396-resistant versions of GRF1/GRF3, resulted in reduced nematode susceptibility (Hewezi et al 2012).…”
Section: Resultsmentioning
confidence: 97%
“…MiR-30 suppresses CSE expression at both mRNA and protein levels, indicating that miR-30 regulates CSE expression by promoting mRNA degradation. On the other hand, Shen et al (31) and Liu et al (21) found that H 2 S participate in different pathological and physiological processes by regulating miRNA expression. These demonstrate that the regulation between H 2 S and miRNA is mutual.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to its roles in metazoans, the overall action of H 2 S is to relieve stress, (Qiao et al 2015), including drought (Jin et al 2011;Christou et al 2013Christou et al , 2014Shen et al 2013); however the underlying mechanisms remain unknown (Pandey 2014). Limited evidence has demonstrated that H 2 S and NO have some overlapping physiological functions in plants ( García-Mata and Lamattina 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, transgenic Arabidopsis plants that ectopically expressed the rat nNOS gene enhanced the expression of stress-responsive genes (such as AtPYL4 and AtPYL5), resulting in drought tolerance (Shi et al 2014). Meanwhile, exogenous NaHS treatment, which is a H 2 S donor, altered the transcriptional reformation of drought associated miRNAs, such as miR167, miR393, miR396 and miR398 and can therefore affect their target gene expressions and thus improve drought tolerance in Arabidopsis (Shen et al 2013). Moreover, understanding the complex NO-and H 2 S-priming effects in plants requires a detailed analysis of both physiological and molecular changes.…”
Section: Introductionmentioning
confidence: 99%